The significant role of leadership development in public educational institutions (Training and Practice : Journal of Educational Sciences, 2020)
The leadership development of public educational institutions has been a current issue and task to be solved for years. I carried out a mini-research related to the topic in 2012 and the purpose of my current paper is to analyse the changes that have taken place since then. The study aims to answer the following questions: Why is this field difficult and unable to develop? Why is this significant knowledge not highlighted in the system of public education and trainings of institute management? Why does it appear only on a theoretical level in most of the trainings? I would like to reflect on the reasons why leaders do not use their theoretical knowledge in practice and what kind of help they get from the maintainer to develop their attitude, method and style of leading. In the research, kindergarten leaders and school principals answered related questions.